Synergy Of Human Capital Management And Technology Information In Improving The Organizational Performace Of PT Bank Tabungan Negara (Persero), Tbk. (BTN) - Bertiana Beatrisia Prastiani; Theodorus Sendjaja (Penerbit dan Percetakan CV.Picmotiv, 2025)
The development of the banking industry demands an increase in the quality of human resources (HR) in line with the utilization of information technology. PT Bank Tabungan Negara (Persero), Tbk. as one of the Himbara Banks that focuses on housing finance, needs to integrate Human Capital Management (HCM) with information technology to improve organizational performance. This study analyzes the synergy between Human Capital Management (HCM) and Information Technology (IT) in improving organizational performance at PT Bank Tabungan Negara (Persero), Tbk. (BTN). The purpose of this study is to identify how an integrated HCM strategy with the utilization of IT can optimize operational efficiency, product innovation, and customer satisfaction, which ultimately impacts the bank's financial and non-financial performance. The research method used is a case study with a qualitative approach, through in-depth interviews with management and staff, as well as internal document analysis. The results show that the integration of HCM and IT at BTN creates efficiency in the employee recruitment and development process, improves data-based decision-making, and accelerates adaptation to market changes. This synergy positions BTN as an agile and highly competitive organization. Indirectly, BTN continues to transform with the development of digital competition, thus having a significant impact on both employees and customers.